1976
DOI: 10.1002/1097-0142(197611)38:5<2017::aid-cncr2820380525>3.0.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Lymph node involvement by direct extension in adenoid cystic carcinoma.Absence of classic embolic lymph node metastasis

Abstract: Thirty-four cases of adenoid cystic carcinoma seen at the University of Virginia Hospital from 1946 to 1974 were reviewed, with special emphasis on lymph node involvement by tumor. Lymph node involvement was found in three cases of primary tumors of the submaxillary gland, and all of the affected lymph nodes were in the immediate vicinity of the primary tumor. Two lymph nodes were involved in two of the cases, and one node was involved in the third case. In all of these lymph nodes, adenoid cystic carcinoma wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0
2

Year Published

1979
1979
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 23 publications
0
23
0
2
Order By: Relevance
“…8 The abundant expression of CXCR4 in the predominantly hematogenously metastasizing ACC suggests that CXCR4 may play a role in directing ACC cells to their metastatic sites. In contrast to the frequent hematogenous dissemination, lymphogenous metastases in ACC are extremely rare, 4,46,47 despite the fact that the lymph nodes are also an abundant source of CXCL12. Although several studies have suggested a role for CXCR4 in lymph node metastasis, [48][49][50] accumulating evidence suggests that CXCR4 is not a major participant in lymphatic tumor spread, including large-scale gene expression data in metastatic head and neck SCC.…”
Section: Discussionmentioning
confidence: 99%
“…8 The abundant expression of CXCR4 in the predominantly hematogenously metastasizing ACC suggests that CXCR4 may play a role in directing ACC cells to their metastatic sites. In contrast to the frequent hematogenous dissemination, lymphogenous metastases in ACC are extremely rare, 4,46,47 despite the fact that the lymph nodes are also an abundant source of CXCL12. Although several studies have suggested a role for CXCR4 in lymph node metastasis, [48][49][50] accumulating evidence suggests that CXCR4 is not a major participant in lymphatic tumor spread, including large-scale gene expression data in metastatic head and neck SCC.…”
Section: Discussionmentioning
confidence: 99%
“…Adenoid cystic carcinomas, although often fatal, are more indolent neoplasms that unlike nonkeratinizing SCCs almost never metastasize to regional lymph nodes. 2,41 Nonkeratinizing SCCs often show continuity with the overlying surface epithelium, are often associated with dysplasia of the overlying epithelium, and often contain foci of keratinization. These features are not found in adenoid cystic carcinomas.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…As mentioned, embolic lymph node metastases are rare with true adenoid cystic carcinoma, which more often metastases hematogenously. 2 Immunohistochemistry is of some value in distinguishing these 2 tumor types when confronted with small biopsy specimens. Over 60% of adenoid cystic carcinomas with a cribriform growth pattern are immunoreactive for smooth muscle actin and even muscle-specific actin.…”
Section: Differential Diagnosismentioning
confidence: 99%
“…This reduces loco-regional recurrence and increases disease free survival rates [8,9]. Metastasis to the lymph nodes is rare and hence neck dissection is usually not warranted [10].…”
Section: Discussionmentioning
confidence: 99%